Silent barriers: The hidden impact of microaggressions on migrant entrepreneurs - Alexandra David; Judith Terstriep (Institut Arbeit und Technik (IAT), 2025)
Microaggressions, subtle yet pervasive forms of discrimination, undermine migrant entrepreneurs by adversely affecting their psychological well-being and hindering their business development. Through a qualitative multiplecase approach, we show how microaggressions - such as avoidance and pathologisation - impact the business success of migrant entrepreneurs in Germany. Our study highlights the compounded challenges of intersecting marginalised identities, urging targeted interventions for inclusive entrepreneurial ecosystems. We call for diverse research and strategies to mitigate microaggressions, urging action by policymakers and practitioners to foster an equitable entrepreneurial landscape.
Keywords: 330; migrant entrepreneurship; minority entrepreneurship; ethical microaggressions; entrepreneurial ecosystems